Web-Based Cash Receipt Accounting System Using the Direct Posting Method (Case Study: SD Putra Nirmala - Cirebon) - Suwandi; Muhamamd Hatta; Willy Eka Septian; Gytha Nurhana (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to make an application for cash receipts for paying tuition fees, building fees and uniform payments at Putra Nirmala Elementary School, Cirebon City. The research method used is the direct posting method, in which cash receipts transactions are recorded directly in the general journal and ledger. This research topic is very important for the school, because it can help manage cash inflows in a computerized manner. The result of this study is the establishment of a cash receipts application that can help schools by using the direct post bookkeeping method. By making this application, it can help the management of Putra Nirmala Elementary School, Cirebon City, in managing cash inflows from paying tuition fees, building fees and uniform payments